A meta-analytic review of correctional interventions for women offenders: gender-neutral versus gender-informed approaches - Gobeil, Renée (Criminal justice and behavior, 2016)
Using meta-analytic approaches, we examined whether interventions for women offenders are effective in reducing recidivism, as well as whether gender-informed and gender-neutral interventions differ in their effectiveness. Across 38 effect sizes reflecting 37 studies and nearly 22,000 women offenders, women who participated in correctional interventions had 22% to 35% greater odds of community success than non-participants. In other words, correctional interventions for women are at least as effective as the published rates for men. Across all 38 effect sizes, gender-informed and gender-neutral interventions were equally effective; however, when analyses were limited to 18 effect sizes associated with studies of higher methodological quality, gender-informed interventions were significantly more likely to be associated with reductions in recidivism. These findings support recent research indicating that women and girls are more likely to respond well to gender-informed approaches if their backgrounds and pathways to offending are associated with gendered issues.